A review of industrial tracking control algorithms. (September 2020) - Yuan, Meng; Manzie, Chris; Good, Malcolm; Shames, Iman; Gan, Lu; Keynejad, Farzad; Robinette, Troy
Abstract: Advanced manufacturing is characterised by machines that move an end effector through a given trajectory to perform operations such as cutting, grinding and printing. In many industrial machines, properties such as structural flexibility, external disturbances as well as spatially separate actuator and end effector make the tracking problem challenging. In this paper, a literature survey on trajectory tracking control algorithms is conducted to examine representative features of existing methods. Then the major classes of algorithms are compared on a commercial single-axis test bench to provide practitioners with a direct insight into the trade-off between performance and implementation. Highlights: Representative features of existing tracking control algorithms are examined. Trade-off of controllers between performance and implementation effort is discussed. A direct insight into the trade-offs is provided based on the experiments.